Hydrogeochemical-Geophysical Responses and Non-seismic Genetic Mechanism of Typical Spring and Well Water Surge in Central and Southern Hebei - Chun-Ling Ji; Bo Dong; An-Pin Zhou; Jun Cao (Applied Geophysics, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Singlet oxygen-dominated non-radical degradation of 2,4-dichlorophenol by peroxymonosulfate activated by Cu-Mg-Fe oxides - Wei-Ling Qiu; Yi-Chin Cho; Yi-Pin Lin (Journal of Environmental Chemical Engineering, 2026)

Comparative analysis of deep learning models for cell counting in microalgae samples - Vimal Angela Thiviyanathan; Pin Jern Ker; Hassan Mohamed; Hasan Firdaus Mohd Zaki; Hui Jing Lee; Shirley G.H. Tang; Kai Ling Yu; Nazlina Haiza Mohd Yasin (Algal Research, 2025)

Geoarchaeological study of the evolution of rice farming fields in prehistoric Yangtze Delta and Huai River regions of China - Yijie Zhuang; Pin Ding; Lina Zhuang; Yonglei Wang; Wenwan Wu; Xia Wang; Yulong Niu; Guoping Sun; Xingtao Wei; Ling Qin (Quaternary Science Reviews, 2025)

Bacterial Community Composition and Prevalence of Aeromonas dhakensis in Four Tilapia Freshwater Aquaculture Systems in Malaysia - Sook Ling Lim; Suat Moi Puah; Siti Nursyuhada Baharudin; Nur Insyirah Mohd Razalan; Kieng Soon Hii; Wei Ching Khor; Yen Ching Lim; Kyaw Thu Aung; Kek Heng Chua; Po Teen Lim; Chui Pin Leaw (Fishes, 2025)
The tilapia (Oreochromis) aquaculture industry in Malaysia has expanded rapidly to meet the increasing demand for animal protein. However, this growth is challenged by microbial infections, particularly those caused by the emerging pathogen Aeromonas dhakensis. This study aimed to investigate the microbial community composition across four distinct tilapia farming systems and assess associated water physicochemical parameters, with a focus on detecting the presence of A. dhakensis and elucidating its environmental associations. Water physicochemical parameters were measured to evaluate environmental conditions, microbial communities were characterized through 16S rDNA metabarcoding, and A. dhakensis was detected using both microbiological and molecular approaches. Principal component analysis (PCA) and canonical correspondence analysis (CCA) were employed to explore the influence of environmental variables and microbial community dynamics on pathogen occurrence. Our results indicated that floating cages exhibited higher levels of temperature, ammonium, and fecal coliform, while cement tanks showed signs of nutrient accumulation. PCA revealed that both systems were associated with degraded water quality. A total of 45 A. dhakensis strains with distinct fingerprints were isolated. The 16S metabarcoding revealed Proteobacteria, Actinobacteria, and Planctomycetota as the dominant phyla. Alpha diversity did not differ significantly among pond systems, while beta diversity revealed variations in microbial assemblages across aquaculture systems. CCA identified dissolved oxygen, temperature, macronutrients (phosphate, ammonium, nitrate, and nitrite), and turbidity as significant environmental drivers shaping the microbial community structure across the pond systems. In conclusion, this study highlights the importance of environmental factors, particularly dissolved oxygen, temperature, and nutrient levels, in shaping microbial community composition and potentially influencing the presence of pathogenic bacteria such as A. dhakensis. These findings underscore the need for improved environmental management in tilapia aquaculture to mitigate disease risks and support fish health.

Enrichment and characterization of foodborne fungal spores by ferric ion-based surface-assisted laser desorption/ionization mass spectrometry - Tzu-Ling Yang; Chih-Wei Chen; Noor Hidayat Abu Bakar; Pin-Chen Pan; Po-Hung Cheng; Yu-Chie Chen (Food Chemistry, 2025)

Differential proteomic profiles between cognitive frail and robust older adults from the MELoR cohort - Siong Meng Lim; Yee Ling Ng; Abu Bakar Abdul Majeed; Maw Pin Tan; Hui Min Khor; Shahrul Bahyah Kamaruzzaman; Kalavathy Ramasamy (GeroScience, 2024)

Synergising hydrothermal pre-treatment and biological processes for enhancing biohydrogen production from palm oil mill effluent - Bidattul Syirat Zainal; Kai Ling Yu; Hwai Chyuan Ong; Hassan Mohamed; Pin Jern Ker; G. Abdulkreem-Alsultan; Yun Hin Taufiq-Yap; TM Indra Mahlia (Process Safety and Environmental Protection, 2024)

Towards automatic urban tree inventory: Enhancing tree instance segmentation via moving object removal and a chord length-based DBH estimation approach - Wai Yi Chau; Jun Kang Chow; Tun Jian Tan; Jimmy WU; Mei Ling Leung; Pin Siang Tan; Siu Wai Chiu; Billy Chi Hang Hau; Hok Chuen Cheng; Yu-Hsing Wang (Computers and Electronics in Agriculture, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

Production and characterization of seaweed-based bioplastics incorporated with chitin from ramshorn snails - Regina Zhi Ling Leong; Swee Sen Teo; Hui Yin Yeong; Swee Pin Yeap; Phei Er Kee; Su Shiung Lam; John Chi-Wei Lan; Hui Suan Ng (Systems Microbiology and Biomanufacturing, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Assessment of sediment transport in Luxiapuqu watershed using RUSLE-TLSD and InSAR techniques: Yarlung Tsangpo River, China - Hao-Shuang Chen; Ling Lan; Yi-Pin Nie; Yu-Ge Wang; Xie-Kang Wang (Environmental Science and Pollution Research, 2024)

Possible germline progenitor cells in extra-gonadal tissues of the sea anemone, Exaiptasia diaphana - Pei-Jung Shao; Yi-Ling Chiu; Pin-Hsuan Tsai; Shinya Shikina (Frontiers in Marine Science, 2023)
Many anthozoans, e.g., sea anemones and corals, have remarkable capacities for asexual reproduction and regeneration, creating complete individual polyps from pieces of parental polyp tissue. Notably, polyps produced asexually (or regenerated) from somatic tissues that originally contain no gonads are capable of sexual reproduction. However, how somatically derived polyps can reproduce remains largely unexplored. Here, using a sea anemone, Exaiptasia diaphana , we show that potential germline progenitor cells are present in the extra-gonadal tissues, and that they are allocated to newly produced individuals during asexual reproduction/regeneration. Histological analysis of E. diaphana demonstrated that polyps asexually produced from pedal lacerates can create mature gametes. Amputation experiments showed that polyps regenerated from the head, which originally lacked gonadal tissue, formed gonads and initiated gametogenesis. Immunohistochemical analysis with a germline marker, vasa, demonstrated the presence of vasa-positive cells in various polyp tissues. These findings suggest that vasa-positive cells in extra-gonadal tissues may be a reservoir of germline progenitor cells to ensure sexual reproductive capacity in individuals produced asexually or regenerated from somatic tissues.

AI-IoT integrated framework for tree tilt monitoring: A case study on tree failure in Hong Kong - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau (Agricultural and Forest Meteorology, 2023)

Curcumin-rich curry consumption and life expectancy: Singapore longitudinal ageing study - Tze Pin Ng; Shwe Zin Nyunt; Qi Gao; Xinyi Gwee; Denise Qian Ling Chua; Keng Bee Yap (GeroScience, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Effect of gradation variation on particle transport process in a generalized flash flood gully via CFD-DEM method - Yi-pin Nie; Ling Lan; Xu-feng Yan; Xie-kang Wang (Acta Geophysica, 2022)

Genome sequencing and comparative genome analysis of 6 hypervirulent Klebsiella pneumoniae strains isolated in China - Ling Du; Jiaxue Zhang; Pin Liu; Xuan Li; Kewen Su; Lingyue Yuan; Zhongshuang Zhang; Dan Peng; Yingli Li; Jingfu Qiu (Archives of Microbiology, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Hydroxychavicol, a polyphenol from Piper betle leaf extract, induces cell cycle arrest and apoptosis in TP53-resistant HT-29 colon cancer cells - Aiysvariyah Rajedadram; Kar Yong Pin; Sui Kiong Ling; See Wan Yan; Mee Lee Looi (Journal of Zhejiang University-SCIENCE B, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

MicroRNA-143–5p modulates pulmonary artery smooth muscle cells functions in hypoxic pulmonary hypertension through targeting HIF-1α - Bi Tang; Ming-ming Tang; Qing-mei Xu; Jian-lu Guo; Ling Xuan; Jing zhou; Xiao-jing Wang; Heng Zhang; Pin-fang Kang (Journal of Biosciences, 2020)

Neogenkwanine I from the flower buds of Daphne genkwa with its stereostructure confirmation using quantum calculation profiles and antitumor evaluation - Xue-Wen Hou; Shuang Han; Ying-Ying Zhang; Hai-Bi Su; Pin-Yi Gao; Ling-Zhi Li; Shao-Jiang Song (Natural Product Research, 2020)

Study on the differential gene expression of elm leaves fed on by Tetraneura akinire Sasaki - Hai-bo Lu; Ling-pin Jin; Dong Wei; Zhi-hong Huang (Genes & Genomics, 2019)

Transcriptome comparative analysis of two Camellia species reveals lipid metabolism during mature seed natural drying - Jin-Ling Feng; Zhi-Jian Yang; Wei-Wei Bai; Shi-Pin Chen; Wen-Qiang Xu; Yousry A. El-Kassaby; Hui Chen (Trees, 2017)

Signaling pathway in development of Camellia oleifera nurse seedling grafting union - Jin-Ling Feng; Zhi-Jian Yang; Shi-Pin Chen; Yousry A. El-Kassaby; Hui Chen (Trees, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Probabilistic framework for assessing the arsenic exposure risk from cooked fish consumption - Min-Pei Ling; Chiu-Hua Wu; Szu-Chieh Chen; Wei-Yu Chen; Chia-Pin Chio; Yi-Hsien Cheng; Chung-Min Liao (Environmental Geochemistry and Health, 2014)

Cadmium Neurotoxicity to a Freshwater Planarian - Jui-Pin Wu; Hui-Ling Lee; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Hazard management and risk design by optimal statistical analysis - Cheng-Wu Chen; Kevin Fong-Rey Liu; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

A novel strategy to determine the insurance and risk control plan for natural disaster risk management - Cheng-Wu Chen; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

Identification of Putative Artemisia annua ABCG Transporter Unigenes Related to Artemisinin Yield Following Expression Analysis in Different Plant Tissues and in Response to Methyl Jasmonate and Abscisic Acid Treatments - Ling Zhang; Xu Lu; Qian Shen; Yunfei Chen; Tao Wang; Fangyuan Zhang; Shaoyan Wu; Weimin Jiang; Pin Liu; Lida Zhang; Yueyue Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Risk and uncertainty analysis in the planning stages of a risk decision-making process - Wen-Ko Hsu; Chun-Pin Tseng; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)